The Impact of Microsoft PowerPoint Online ‘Rehearse with Coach’ Feature in Improving BEC Students’ Presentation Skills - Jariyah A, Ainun; Patak, Andi Anto; Novia, Lely (Program Studi Pendidikan Bahasa Inggris FBS UNM, 2025)
The purpose of this study is to evaluate the impact of using the “Rehearse with Coach” feature in Microsoft PowerPoint on the presentation skills of Business English Communication students. This research used a qualitative case study method with thematic analysis, involving 10 Business English Communication students from Makassar State University. Data were collected through semi-structured interviews and observations. The results showed that this feature significantly improved students' presentation skills. Students also rated the real-time feedback provided by the feature as very practical and helpful for immediate improvement, although there were some suggestions to improve the accuracy of error detection and responsiveness to external distractions. This research makes an important contribution to the understanding of how digital tools such as “Rehearse with Coach” can improve presentation skills.